Digital twin in industry 4.0: technologies, applications and challenges - Pires, Flávia (2020)
The digital transformation that is on-going world-wide, and triggered by the Industry 4.0 initiative, has brought to the surface new concepts and emergent technologies. One ofthese new concepts is the Digital Twin, which recently started gaining momentum, and is related to creating a virtual copy ofthe physical system, providing a connection between the real and virtual systems to collect and analyze and simulate data in thevirtual model to improve the performance of the real system. The benefits of using the digital twin approach is attracting significant attention and interest from research and industry communities in the last few years, and its importance will increase in the upcoming years. Having this in mind, this paper surveys and dis-cusses the digital twin concept in the context of the 4th industrial revolution, particularly focusing the concept and functionalities, the associated technologies, the industrial applications and theresearch challenges. The applicability of the digital concept isillustrated by the virtualisation of an UR3 collaborative robot which used the V-REP simulation environment and the Modbus communication protocol